Isolation, identification and antibiotic sensitivity pattern of the uterine secretions in cows with metritis - INGAWALE, M V; DHOBLE, R L; DHOBLE, R L; SAWALE, A G (The Indian Journal of Animal Reproduction, 2003)
Microbial agents were isolated from forty eight cases of metritis and recorded their antibioticsensitivity pattern. Cornybacterium species were the most prevalent followed by E. coli and thenPseudomonas. Maximum percent of uterine isolates were sensitive to Ciprofloxacin, Enrofloxacin andGentamycin and were resistant to Ampicillin and Sulphamethaxazole.
Keywords: Metritis; Antibiotic sensitivity; Cows